2008
DOI: 10.1002/jssc.200700442
|View full text |Cite
|
Sign up to set email alerts
|

Separation and quantitation of several angiotensin II receptor antagonist drugs in human urine by a SPE–HPLC–DAD method

Abstract: In this work, an SPE-HPLC method coupled to photodiode array detection was validated in human urine matrix, in order to monitor four antihypertensive angiotensin II receptor antagonist drugs in patients under cardiovascular treatment. For that purpose, experimental design was used. Quantitation was accomplished by the internal standard method. The obtained LOQs were 95, 113, 125, and 85 ng/mL for eprosartan, telmisartan, irbesartan, and valsartan, respectively. The intraday and interday precision and accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In conclusion, by evaluating some key points of this on-line SPE-MS/MS method in comparison with previous methods developed for the quantitation of ARA-II in biological matrices and more particularly valsartan and candesartan [5,[7][8][9][11][12][13][14], we found that with the very low volume of biological sample used, it is among the most sensitive described methods. Moreover, to our knowledge it presents also the shortest analysis run time including chiefly the sample clean-up.…”
Section: System Ruggednessmentioning
confidence: 97%
See 1 more Smart Citation
“…In conclusion, by evaluating some key points of this on-line SPE-MS/MS method in comparison with previous methods developed for the quantitation of ARA-II in biological matrices and more particularly valsartan and candesartan [5,[7][8][9][11][12][13][14], we found that with the very low volume of biological sample used, it is among the most sensitive described methods. Moreover, to our knowledge it presents also the shortest analysis run time including chiefly the sample clean-up.…”
Section: System Ruggednessmentioning
confidence: 97%
“…Single analytes in biological matrices were extracted by liquid-liquid extraction [5], solid phase extraction (SPE) [6][7][8][9][10] or protein precipitation [11][12][13]. Extracts were assayed by liquid chromatography with ultra-violet absorbance detection (LC-UV) [6,7], fluorescence detection (LC-Fluo) [5,8,13] or mass spectrometry with electrospray ionization (ESI-MS) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [6] quantified HCTZ and another ARB, valsartan, by use of a tandem mass spectrometric method; their quantification limits were 1 and 4 ng mL -1 for HCTZ and valsartan, respectively. IRBE LOQ described in the literature are 0.78, 3, 15, and 125 ng mL -1 , respectively, for an LC-MS-MS method [8], fluorescence detection [15], solid-phase microextraction with HPLC-DAD [29], and an SPE-HPLC-DAD method for urine [30].…”
Section: Methods Validationmentioning
confidence: 99%
“…Based on the recent literature, most of the publications deal with the determination of the following compounds in the ARB group -Valsartan, both for pharmaceutical formulations [3][4][5][6][7] and biological material: plasma 5,8 and urine. 9 It is normally determined by HPLC method with C18 column and UV-VIS detector 3,6 , mass spectrometry (MS) detector 5 or fluorescence detector. 4 It is also determined spectrophotometrically 9 and with TLC.…”
Section: Introductionmentioning
confidence: 99%